(untitled) (The Review of Diabetic Studies, 2025)
OBJECTIVES: One of the main causes of physical disability is stroke, and 80% of stroke survivors suffer upper extremity dysfunction characterized by reduced muscle strength and functional limitation in muscle control and life quality. Arm ability training with biofeedback techniques is reported to enhance the functional recovery of the upper limb by improving the dexterity of the upper limb and life quality. METHODS: An experimental study to find out the effects of Arm Ability Training with Biofeedback techniques on upper limb dexterity, functional ability, and quality of life in sub-acute stroke survivors. Sixty participants were chosen and randomly allocated to two groups. Group A received Arm ability training with biofeedback techniques, and Group B received conventional therapy for 60 minutes, 5 days/week for 3-4 weeks. The outcome measures were Modified standardized nine-hole peg test (mS-NHPT), Fugl-Meyer Assessment Upper Extremity, 12-item stroke-specific quality of life scale, and Wolf Motor Function Test. RESULTS: The mean completion time for the m-S NHPT decreased (from 113.78 ± 3.14 to 88.36 ± 2.49), and the FMA-UL increased (from 79.08 ± 2.54 to 90.52 ± 2.92). SS-QOL-12 (19.76 ± 0.99 to 40.12 ± 1.24), WMFT (Functional Ability) (from 46.76 ± 1.47 to 56.92 ± 2.03), and the time score improved (from 478.64 ± 2.9 to 435.16 ± 2.22). The variables indicates a statistical significance (p < 0.05). CONCLUSION: The above result statistically shows significant improvements in dexterity, functional ability, and life quality of sub-acute stroke subjects.